Peningkatan Keterampilan Menulis Teks Biografi Melalui Penerapan Metode Quantum (Tandur) pada Siswa Kelas X SMA Yayasan Purwa Bhakti Ciawi Bogor - Eri Sarimanah; Muh. Rizky Ali Nashir (Triangulasi: Jurnal Pendidikan Kebahasaan, Kesastraan, Dan Pembelajaran, 2021)
The aim of the research is to know the improvement of writing biography text through method of quantum (TANDUR) and to improve the effectiveness of the students study in writing biography text for grade 10 students of Yayasan Purwa Bhakti Ciawi Bogor. The hypothesis of this research is the there is improvement and the effect of student’s ability to write the biography text through method of quantum (TANDUR). The hypothesis can be accepted and be showed with the score average from the students and also can be showed with the result of observation that be done by two collaborators to know the effectiveness of students study. The writing skill in writing biography text can be improved after the researcher used the quantum (TANDUR) as the method in learning process. That was showed with increasing of the score average in each and every cycle. The score average of pre-test is 59,8 or 60% in percentage. In cycle I obtained the increasing of the score average become 72 or 72% and in cycle II obtained the significant score 81,6 or 82%. The success of writing ability in writing biography text after be applied of quantum (TANDUR) method in classroom action research showed the improvement with the score average 82%. In addition, the difference significantly between the results of test in cycle I obtained 72% and 82% in cycle II. It showed successfulness in applying the method of quantum (TANDUR) through improve the writing ability in writing biography text.